OCIMUM GRATISSIMUM L.: A MEDICINAL PLANT WITH PROMISING ANTIUROLITHIATIC ACTIVITY (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Ocimum gratissimum L. has been used to treat various diseases including urinary stone diseases, since ancient time in India. The inhibition of in-vitro calcium-oxalate crystal formation by Ocimum gratissimum L. extract was investigated by different methods i.e nucleation assay and synthetic urine assay. In nucleation assay, the aim was to evaluate the effectiveness of different concentrations of the extract (100-1000 mg/ml) on calcium oxalate crystallization in-vitro while in synthetic urine method the percentage inhibition and growth of the calcium oxalate monohydrate crystals from synthetic urine at different % concentrations of extract (25-100%) was investigated. In both the assay % inhibition for calcium oxalate crystal formation was found directly proportional to the increase in concentration of the plant extract with maximum inhibition of 66.08% at 1000 mg/ml, while in synthetic urine assay maximum inhibition was 62.07 % at 100% concentration of extract. Thus Ocimum gratissimum L. was found to be a potent and promising antiurolithiatic agent, which is in accordance with its use in traditional medicine.